Efektivitas Larutan Desinfektan Dalam Menginaktivasi Virus Avian Influenza pada Bulu Unggas - Bagus Nanang Luwito; I Wayan Teguh Wibawan; Retno Damayanti Soejoedono (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2018)
Avian Influenza (AI) virus is pathogenic agent that can spread from one area to another area through the transportation of infected animals or their products such as feathers. This research was aimed to inactivated AI virus with 775 ppm sodium hypochlorite and 0.1% chloroxylenol to examine the difference of treatment by time (day) for inactivation AI virus on the feathers. AI virus isolate A/chicken/sidrap/ 07160336‐2/2016 used in this research was obtained from Balai Besar Veteriner Maros. The treatment of disinfectants were performed on the first day (the day of disinfectan solutions were prepared), the third day and the seventh day by soaked the feathers in disinfectant solution for 10 minutes. The effectiveness of disinfectans were evaluated by inactivation index. The result show that the average of inactivation index of 775 ppm of sodium hypochlorit was 4.17 for the first day, 5.17 for the third day, and 4.20 for the seventh day, while the average of inactivation index of 0.1% chloroxylenol was 5.50 for the first day, 6.43 for the third day, and 5.77 for the seventh day. Our result indicated that the sodium hypochlorit and chloroxylenol were effective for inactivation of AI virus. The 0.1% of chloroxylenol was more effective for inactivation AI virus than 775 ppm of sodium hypochlorit, whilst the most effective duration for the treatment is the three days.